Gastroduodenal tuberculosis: a case series and a management focused systematic review. (2nd January 2021) - Shah, Jimil; Maity, Pranab; Kumar-M, Praveen; Jena, Anuraag; Gupta, Pankaj; Sharma, Vishal
ABSTRACT: Introduction: Gastroduodenal tuberculosis is an uncommon form of abdominal tuberculosis. Areas covered: We report our experience with five cases of gastroduodenal tuberculosis and present results of a systematic review on gastroduodenal tuberculosis regarding clinical presentation, endoscopic, imaging findings, and the diagnostic and therapeutic approach. Expert opinion: The presentation of gastroduodenal tuberculosis is diverse and may include nonspecific abdominal pain or dyspepsia like symptoms apart from gastric outlet obstruction. Endoscopy may show presence of growth, ulcer, narrowing, or fistula on endoscopy. Endoscopic biopsy, well-biopsy, or mucosal resection of an elevated lesion are helpful. On microscopy, granuloma with or without acid fast bacilli positivity can be found. For treatment, standard antitubercular therapy should be given for 6 months. In patients with tight stricture, endoscopic balloon dilatation can be helpful. Surgery is reserved for patient with diagnostic dilemma, refractory stricture, or complications like perforation or fistula. Future research should focus on improving diagnosis with use of modern microbiological techniques like PCR and Xpert MTB/RIF.